Radiographic evaluation of vessel count and density with quantitative magnetic resonance imaging during external breast expansion in Asian women: A prospective clinical trial. Issue 12 (December 2016) - Myung, Yujin; Kwon, Heeyeon; Pak, Changsik; Lee, Hobin; Jeong, Jae Hoon; Heo, Chan Yeong
Summary: Background: Breast augmentation with fat transfer does not bear the risks associated with silicone implantation. The method can potentially be especially useful in Asian women, who often reject augmentation mammoplasty with implants. This prospective clinical trial evaluated the effects of external breast expansion on breast density and vessel count using magnetic resonance imaging. Methods: Thirty-four enrolled patients were instructed to apply one of two devices, the conventional BRAVA device (used in the AESTES trial) or a novel external expansion device (EVERA) designed for Asian women, continuously for 8 h per day for 12 weeks. For external expansion, the pressure was set to 25 mmHg. Follow-up examinations were performed for 4 weeks after completion of the expansion. The ratio between the fibroglandular and adipose tissues of the breast was measured using T1-weighted MRI, and the number of vessels in the breast tissue was determined before and after the treatment by contrast MRI. Additionally, the volume of the breast was measured by laser scanning before, during, and after the device application. The obtained measurements were compared within and between the groups at different time points. Results: Six patients dropped out, while 28 completed the trial without major side effects or adverse events. External expansion significantly increased breast vessel count in both the EVERA and AESTES groups (p = 0.019, p = 0.022). However, it did not significantly change breast density in either group (p = 0.186, p = 0.638). No significant intergroup differences were noted in vessel count (p = 0.874) or density (p = 0.482). Breast volume increases after 12 weeks of application were statistically significant in both groups, with mean changes of 81 ± 22 cc (AESTES) and 98 ± 30 cc (EVERA) (p < 0.001 in both cases). Conclusions: External expansion resulted in a marked increase in breast vessel count but did not affect breast density. The observed increase in breast volume can be considered substantial for Asian women. Level of evidence: Level II, therapeutic study.